PENGARUH PENGETAHUAN, KEPERCAYAAN, DAN GAYA HIDUP TERHADAP MINAT KEPEMILIKAN KARTU KREDIT SYARIAH (Studi Empiris Fakultas Ekonomi dan Bisnis UMJ - Siti Jamilah; Syifa Aulia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze the influence of knowledge, belief, and life style on the interest in ownership of Islamic credit cards. The data used in this study are primary data collected from 84 respondents of class employees and alumni of Islamic Economics. The sampling technique used in the study was nonprobability sampling with purposive sampling type, then the data was processed using multiple linear regression analysis. The results of this study indicate that knowledge, belief and lifestyle partially have a positive and significant effect on the interest in ownership of Islamic credit cards.